Finding of the optimal parameters of animated and stereographic rainbow diffractive images - Borisov, I.S.; Girnyk, V.I.; Kostyukevych, S.A.; Grygoruk, V.I.; Kostyukevych, K.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
We have considered the basic aspects of the technology of animated and
stereographic rainbow images. These images can be included in Optical Security Devices
(OSDs) in order to increase their structure complexity and to improve their protective
properties. The cited technology provides, on the one hand, a simple identification on the
visual level of verification and, on the other hand, the sufficient reliability against
counterfeits. The last property is achieved at first by the division of the elemental unit on
elemental regions of any adjusted shape with outline of the precision that is inaccessible
for the recreation without Electron Beam Lithography Equipment (EBLE) which is used
for the recording of OSDs. Second, the used encoding methods also assure the certain
reliability.

In the context of the paper, the theoretical discussion based a quantitative formulation of
the Huygens--Fresnel law of the diffraction on an elemental diffractive grating is carried
out. For other definite Conditions of Lighting and Observation of Diffracting Light
(CLODL), the correlation between the slope angle of diffraction grating strokes and the
corresponding horizontal parallax angle is got; and the parameter which defines the
channel selection (the quality of splitting into separate channels) is introduced. The rule
for the definition of the wavelength and the intensity of light that diffracts on a given
grating under certain CLODL is derived as well. This fact allows one to create the
software utility that models the behavior of anigrams or stereograms.
An algorithm of the synthesis of anigrams and stereograms as parts of OSDs using the
technology of a composite “figure” elemental unit (that is composed from parts of any
shape) and applying the halftone encoding by the period, filling, and achromaticity or all
these parameters at once is elaborated, and its software implementation is constructed.
The criteria for the choice of such anigram’s parameters as the resolution, number of
channels, and angle distances between them are elaborated. In order to check them, the
results of tests are summarized. The investigation of the optimal parameters of halftone
images’ encoding finding is implemented, and the results obtained for the tough and
flexible linkings of a channel to the subregion of an elemental unit for hatching images
are compared.